PERAN SUPERVISI AKADEMIK DALAM MENDORONG REFLEKSI DIRI GURU PADA PROSES PEMBELAJARAN - Elva zahrotunnaqiyahi; Fakhrudin Ultsa; Ila Rosmilawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving the quality of learning is inseparable from teachers' ability to reflect on their teaching practices. Self-reflection is an important part of teachers' continuous professional development, as it allows them to identify their strengths and weaknesses and design improvements to their teaching. One instrument that has the potential to encourage teachers' reflective abilities is academic supervision. However, the implementation of academic supervision in the field is still often oriented towards administrative and evaluative aspects, so it is not yet optimal in fostering a culture of self-reflection among teachers. This study aims to examine in depth the role of academic supervision in encouraging teachers' self-reflection in the learning process. This study uses a qualitative approach with a holistic single case study design. The research was conducted at Al-Bayan Anyer Islamic Boarding School High School, which was selected purposively because it has a relatively systematic implementation of academic supervision. The research subjects consisted of one supervisor and five teachers who actively participated in academic supervision activities. Data collection was carried out through in-depth interviews, non-active participant observation, and documentation analysis. The data obtained were analyzed using thematic analysis techniques through data reduction, data presentation, and conclusion drawing. The results of the study indicate that academic supervision plays an important role in encouraging teachers to engage in self-reflection when it is carried out using a collaborative approach and is oriented towards mentoring. Academic supervision that emphasizes constructive feedback and reflective questions can help teachers develop critical awareness of their teaching practices. Conversely, supervision that focuses on control and administrative compliance is less effective in fostering teachers' reflective abilities. This study concludes that academic supervision has a strategic role as a means of facilitating teachers' professional development.